Desain Masker Nonmedis dengan Pendekatan Metode QFD dan TRIZ - Antoinette Michaela Goratha; Iwan Halim Saputra (Jurnal Titra, 2021)
The Covid-19 pandemic that is happening all around the world has led into a huge chaos on systems. WHO (World Health Organization) provides recommendations on what features should be considered in the manufacture of non-medical masks. The desire of public (customers) is also considered important in determining the design of non-medical masks. Voice of customers on the design of non-medical masks which are found out using questionnaires. The results of the questionnaire or voice of the customer are then processed using Quality Function Development. Then try to solve the contradicting functions using TRIZ. The characteristics of non-medical masks that are desired by the public are masks that cover the nose and mouth, comfortable earloops, masks that block droplets, masks that have good durability and are not easily damaged, masks have no barriers and can breathe easily, keep the user's nose and mouth dry, according to the price, adjust the shape of the mask, and adjust the design. Of the three non-medical mask design proposals, non-medical mask design 1 is the result of a design that is widely chosen by the community because it is in accordance with their wishes and is considered safer.